2015
DOI: 10.11604/pamj.2015.21.251.6908
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian vein thrombosis

Abstract: Ovarian vein thrombosis (OVT) is a rare cause of abdominal pain that may mimic a surgical abdomen. It is most often diagnosed during the postpartum period. In this report, we present four cases of postoperative ovarian vein thrombosis. The complications of OVT can be significant, and the diagnosis relies on a careful examination of the radiographic findings. It can occur with lower quadrant abdominal pain, especially in the setting of recent pregnancy, abdominal surgery, pelvic inflammatory disease, or maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 16 publications
0
49
1
4
Order By: Relevance
“…This condition involves the right vein more commonly than the left. Ovarian vein thrombosis often has a vague and variable presentation, and a high index of suspicion is required to make the diagnosis [8]. Some patients will have nonspecific symptoms, including malaise, vague diffuse abdominal pain, or dyspnea; others will present with fever and lower quadrant pain [9].…”
Section: Resultsmentioning
confidence: 99%
“…This condition involves the right vein more commonly than the left. Ovarian vein thrombosis often has a vague and variable presentation, and a high index of suspicion is required to make the diagnosis [8]. Some patients will have nonspecific symptoms, including malaise, vague diffuse abdominal pain, or dyspnea; others will present with fever and lower quadrant pain [9].…”
Section: Resultsmentioning
confidence: 99%
“…Once proadhesive surface of subendothelial matrix appeared, its components, adhesive proteins (von Willebrand factor, collagen, fibrinogen, and so on), are immediately involved in the process of forming a primary (cardio-thrombocytic) thrombus followed by hemocoagulation [53]. In the period of pregnancy, the following factors serve as the basis for phlebothrombosis development: physiological hypercoagulation, increase of blood viscosity, formation of blood stasis in the veins of the pelvis and low extremities together with the changes of hormonal status and topographoanatomical interrelations of the pelvic vessels and organs [54][55][56][57][58][59][60].…”
Section: Reviewsmentioning
confidence: 99%
“…Investigations showed that in 80% of cases the right ovarian vein is thrombosed, damage of both ovarian veins is registered in 14%, and isolated thrombosis of the left ovarian vein in 6% of cases. The occurrence of pulmonary artery embolism with underlying ovarian vein thrombosis varies within 0.15-0.33% with fatal outcomes up to 4% in patients with pulmonary thromboembolism [59][60][61][62][63]. At present, the most commonly used classification of VVP is one recommended by the Russian Association of Phlebologists (2013) [2].…”
Section: Reviewsmentioning
confidence: 99%
“…Eine sehr seltene Ursache für Fieber post partum innerhalb der ersten 7 Tage ist die Ovarialvenenthrombose. Sie findet sich in 0,02 % nach vaginalen Geburten und in 0,1-2 % nach der Sectio caesarea [19]. Hierbei scheint ein Zusammenhang mit einer bakteriellen entzündlichen Reaktion zu bestehen, die in die Adnexe abszediert.…”
Section: Ovarialvenenthromboseunclassified